(untitled) (Papeles, 2014)
The purpose of this article is to consider from an ethical perspective some of the possible misunderstandings and omissions of civic education. The definitions in this field of education, the extension of its limits and its validity, require a permanent analysis not only because of the rapid changes of values that characterize our societies but, as critical pedagogy has shown, because of the interest of these societies in watching over its limits and in controlling its expansion. If we consider teaching as an essentially ethical activity, it will be important to detect the possible fields of application of the concept of civism that it tries to implement, to discover who are partially or totally “forgotten” by it, and those who are excluded from its programs. These exclusions express or perhaps prepare a situation by which certain social groups will find themselves limited in their rights and deprived of their dignity.